Political Crime as a Legal and Criminal Category - Kuczur, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
Political crimes, even though they were not ‘explicitly’ defined by the legislator in the contemporary code solution of June 6, 1997, constitute a specific set of prohibited acts, undertaken by the perpetrator under specific political and social conditions. In the criminal code of 6 June 1997, the legislator distinguished the factual states of acts directed against the state (similarly in the Criminal Code of 1969 and the Penal Code of 1932), which bear the features of punishable acts of a political nature. In the interwar period, the acts were specified in two ordinances of the President of the Republic of Poland from 1928 and 1934, penalizing the crime of espionage, and in the penal code of 1932. The typification of these acts was not too complicated and was quite uniform. After 1944/1945, the term ‘counter-revolutionary crime’ was coined in the doctrine of communist criminal law. The nature of the decrees of 1944–1946 settling with the past dominated the interpretations of this concept until 1956. After the October coup, this prohibited act was treated differently. At that time, there was a departure from hyper-criminalization and hyper-penalization of similar behaviors in favor of the persistence of pro-criminalization and pro-penalization tendencies. Doctrinal considerations on the treatment of acts defined as counter-revolutionary crimes dominated at that time its criminal characteristics. A counter-revolutionary act was always a political act. Forcing the penal code of 1969 into the legal system of the state organized the catalog of political acts directed against the state. They were already defined in the title of a chapter of the 1969 Penal Code – as crimes against the political and economic interests of the state. After the breakthrough of 1989 and the initiation of the process of systemic deconstruction, the legislator was faced with the challenge of rehabilitation of people sentenced for (political) activities for the sake of the independent existence of the Polish state and the issue of the settlement of previous criminal (political) state activities. Finally, in the Penal Code of 1997, Art. 127–137 (9) a list of acts against the state that should be defined as political crimes was defined.